Discussion on Neoliberalism & the Marketisation of Social Housing: A Study of Four Countries - S. P. Taylor (New Horizons in Education and Social Studies Vol. 9, 2021)
The rise of Neoliberalism since the late Twentieth century as the dominant global political and economic ideology has impacted on the social housing sectors in different countries. This ideology has introduced market forces to the provision of social housing which has historically been associated with service provision to fulfil a societal need. This chapter builds an earlier paper that looked at the experiences of four countries to understand the impact that marketisation has had on the social housing sector within those countries. The countries chosen have got a number of shared historical commonalities although each has evolved within their own context. The countries looked at are: the Netherlands, United States of America (USA), Australia and United Kingdom (UK). Text has been added to update the details of the study including the conclusion which assesses how the impact of market forces within housing has been aligned to the drive by the underlying thrust of a Neoliberal agenda to reduce the role of the state in these countries. The role of the state in the provision of social housing has reduced across different countries reflecting the global impact of Neoliberalism on their political and economic systems. The nature of such change has to be seen within the historical and operational context of each country.